Determinasi Kualitas Informasi Akuntansi Pada Umkm Di Kabupaten Boyolali, Jawa Tengah - Nur Endah Fajar Hidayah; Irkham Azidan Ajinawa; Aris Eddy Sarwono; Dewi Saptantinah Puji Astuti (Journal Of Management, Business And Education, 2022)
This study aims to determine the effect of financial literacy, financial inclusion, ability to prepare financial reports, and MSME financial performance on the quality of accounting information. The type of research used in this research is quantitative research with a primary data type. Primary data was obtained through the distribution of questionnaires to respondents. The questionnaire was measured using a Likert scale. The population of this study is the owners and actors of MSMEs in the Sawit District of Boyolali Regency totaling 144 MSMEs and the sample is taken using the purposive sampling technique so that there are 113 MSMEs that meet the requirements. The results of the instrument test state that the data is valid and reliable. The goodness of fit test results states that the fit research model and the partial test results state that financial literacy has a significant positive effect on the quality of accounting information but the inclusion of financial and the ability to prepare MSME financial reports to have no effect on the quality of accounting information. The limitation of this research is that it only uses MSME objects in one sub-district in Boyolali so it has not been able to describe the state of MSMEs in all Boyolali districts.